Consumer Perceptions of Online Shopping Experiences Through the Shopee Application - Meisya Umadi Putri; Pinkan Ajeng Anggella; Fikri Rizki Utama (Takaza Innovatix Labs Ltd., 2026)
This study aims to analyze students’ perceptions of online shopping experiences through the Shopee application at the State Islamic University of Jurai Siwo Lampung. The research used a descriptive qualitative method through interviews with three students from different faculties. The results indicate that ease of use, transaction security, attractive promotions, and service quality are key factors shaping consumers’ positive perceptions. A pleasant shopping experience significantly influences user satisfaction and loyalty. Shopee is considered successful in creating an efficient, safe, and youth-oriented online shopping experience.